2021
DOI: 10.17161/rrnmf.v2i5.15806
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns in the management of myasthenia gravis: a cross-sectional survey of neurologists in the United States

Abstract: Background: Management of myasthenia gravis (MG), a rare immunoglobulin G autoantibody–mediated neuromuscular junction disorder, is driven by physician experience. To gain insight into current practices and physician needs, neurologists’ use of guidelines and disease activity evaluations to manage MG was assessed. Methods: In November and December of 2020, a quantitative, cross-sectional, 51-item, online survey–based study was used to collect data from 100 community neurologists, from 31 US states, who treat M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Physician reported patterns for myasthenia management also varies; a recent online survey of over 100 community neurologists found that many neurologists may rely more on clinical judgment than on consensus-based guidelines. 30 In addition, there are hospital and system-level factors that may contribute to thymectomy utilization, such as the availability of local neuromuscular and surgical expertise, which likely explain our findings regarding hospital size and teaching status. Finally, NIS is an administrative database that uses codes produced for billing purposes.…”
Section: Discussionmentioning
confidence: 92%
“…Physician reported patterns for myasthenia management also varies; a recent online survey of over 100 community neurologists found that many neurologists may rely more on clinical judgment than on consensus-based guidelines. 30 In addition, there are hospital and system-level factors that may contribute to thymectomy utilization, such as the availability of local neuromuscular and surgical expertise, which likely explain our findings regarding hospital size and teaching status. Finally, NIS is an administrative database that uses codes produced for billing purposes.…”
Section: Discussionmentioning
confidence: 92%